Liver metastasis or a pseudocyst? A rare presentation of leiomyosarcoma’s metastasis in the liver - Bednarek, Adrian; Sołek, Julia; Szymczyk, Konrad; Gwardys, Mikołaj; Wierzchniewska-Ławska, Agnieszka; Jesionek-Kupnicka, Dorota; Braun, Marcin; Romańska, Hanna M. (Contemporary Oncology/Współczesna Onkologia, 2022)
Gastrointestinal neoplasms most commonly metastasize to the liver, where they are typically found as solid and hypervascular lesions. Here, we describe a case of a 44-year-old man with a leiomyosarcoma of the rectum, who at the time of diagnosis presented with a small (5 mm in diameter) cyst-like lesion in the liver. Positron emission tomography demonstrated no increased metabolism in the area of the cyst, suggesting a benign character of the lesion. However, after 3 years, CT scans revealed enlargement of the cyst, and local surgical excision was performed. The results of histopathological examination of the resected material were consistent with metastatic leiomyosarcoma. Subsequently, the patient developed lung metastases and died within 2 years. Our case describes a very rare presentation of leiomyosarcoma’s metastasis that led to an ill-fated misdiagnosis and dismal disease outcome.